Reconstructing post-Jurassic overburden in central Europe: new insights from mudstone compaction and thermal history analyses of the Franconian Alb, SE Germany - Freitag, Simon; Drews, Michael; Bauer, Wolfgang; Duschl, Florian; Misch, David; Stollhofen, Harald (Solid Earth, 2022)
The Franconian Alb of SE Germany is characterized by large-scale exposures of Jurassic shallow marine limestones and dolostones, which are frequently considered to be outcrop analogues for deep geothermal reservoir rocks in the North Alpine Foreland Basin farther south. However, the burial history of the Franconian Alb Jurassic strata is not well known as they were affected by emersion, leading to extensive erosion and karstification with only remnants of the original Cretaceous and Cenozoic cover rocks preserved. To estimate the original thicknesses of the post-Jurassic overburden we investigated the petrophysical properties and the thermal history of Lower and Middle Jurassic mudstones to constrain their burial history in the Franconian Alb area. We measured mudstone porosities, densities, and maturities of organic material and collected interval velocities from seismic refraction and logging data in shallow mudstone-rich strata. Mudstone porosities and P-wave velocities vertical to bedding were then related to a normal compaction trend that was calibrated on stratigraphic equivalent units in the North Alpine Foreland Basin. Our results suggest maximum burial depths of 900-1700 m, 300-1100 m of which is attributed to Cretaceous and younger sedimentary rocks overlying the Franconian Alb Jurassic units. Compared to previous considerations this implies a more widespread distribution and increased thicknesses of up to similar to 900 m for Cretaceous and up to similar to 200 m for Cenozoic units in SE Germany. Maximum overburden is critical to understand mechanical and diagenetical compaction of the dolostones and limestones of the Upper Jurassic of the Franconian Alb. The results of this study therefore help to better correlate the deep geothermal reservoir properties of the Upper Jurassic from outcrop to reservoir conditions below the North Alpine Foreland Basin. Here, the Upper Jurassic geothermal reservoir can be found at depths of up to 5000 m.
CRIS-Team WoS Importer:2022-07-22